Preclinical trial comparing radiotherapy alone versus standard radiochemotherapy in three human papilloma virus (HPV) negative and three HPV-positive head and neck squamous cell carcinoma (HNSCC) xenograft tumour models - Valentini, Chiara; Ebert, Nadja; Koi, Lydia; Pfeifer, Manuel; Löck, Steffen; Erdmann, Christoph; Krause, Mechthild; Baumann, Michael (Radiotherapy and oncology, 2023)
Purpose - To perform a preclinical trial comparing the efficacy of fractionated radiotherapy versus radiochemotherapy with cisplatin in HPV-positive and negative human head and neck squamous cell carcinoma (HNSCC) xenografts. - Material and methods - Three HPV-negative and three HPV-positive HNSCC xenografts in nude mice were randomized to radiotherapy (RT) alone or to radiochemotherapy (RCT) with weekly cisplatin. To evaluate tumour growth time, 20 Gy radiotherapy (±cisplatin) were administered in 10 fractions over 2 weeks. Dose-response curves for local tumour control were generated for RT with 30 fractions over 6 weeks to different dose levels given alone or combined with cisplatin (RCT). - Results - One of three investigated HPV-negative and two out of three HPV-positive tumour models showed a significant increase in local tumour control after RCT compared to RT alone. Pooled analysis of the HPV-positive tumour models showed a statistically significant and substantial benefit of RCT versus RT alone, with an enhancement ratio of 1.34. Although heterogeneity in response to both RT and RCT was also observed between the different HPV-positive HNSCC, these overall were more RT and RCT sensitive than HPV-negative models. - Conclusion - The impact of adding chemotherapy to fractionated radiotherapy on local control was heterogenous, both in HPV-negative and in HPV-positive tumours, calling for predictive biomarkers. RCT substantially increased local tumour control in the pooled group of all HPV-positive tumours whereas this was not found in HPV-negative tumours. Omission of chemotherapy in HPV-positive HNSCC as part of a treatment de-escalation strategy is not supported by this preclinical trial.
Online verfügbar 20. Februar 2023, Artikelversion 1. März 2023
Gesehen am 06.06.2023